2014
DOI: 10.1039/c4an00980k
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic scaffolds for highly selective ion sensing/removal of Co(ii), Cu(ii), and Cd(ii) ions in water

Abstract: High exposure to metals, such as cobalt (Co), copper (Cu) and cadmium (Cd), potentially has adverse effects, and can cause severe health problems, leading to a number of specific diseases. This study primarily aims to monitor, detect, separate, and remove the trace concentrations of Co(II), Cu(II), and Cd(II) ions in water, without a preconcentration process, using aluminosilica optical sensor (ASOS) monoliths. These monolithic scaffolds with advantageous physical features (i.e., large surface area-to-volume r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 100 publications
(70 reference statements)
0
27
0
Order By: Relevance
“…Uptake efficiencies for MSA-1, MSA-2, and MSA-3 were calculated as % (C A /C 0 ), where C A is the target ion concentration uptake by solid MSAs and C 0 is the initial target ion concentration. Results indicated that the functionalities of the wagon-wheel-shaped MSAs were maintained over eight regeneration/reuse cycles 46,47 .…”
mentioning
confidence: 88%
“…Uptake efficiencies for MSA-1, MSA-2, and MSA-3 were calculated as % (C A /C 0 ), where C A is the target ion concentration uptake by solid MSAs and C 0 is the initial target ion concentration. Results indicated that the functionalities of the wagon-wheel-shaped MSAs were maintained over eight regeneration/reuse cycles 46,47 .…”
mentioning
confidence: 88%
“…The juxtaposition of copper ions as biologically necessary and environmentally toxic means that selective and sensitive monitoring of copper ions is important for human health and industrial activity . In this context Cu(II) selective chemosensors and chemodosimeters are highly prized and a variety of detecting platforms have been developed including gold and carbon nanoparticle probes, mesoporous materials and enzymatic systems . Whilst transition metal ion sensors generally rely on metal ion binding, chemodosimetric Cu(II) detection is receiving increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…Sewage usually receives mixed effluents from industries, households, and hospitals; these effluents pollute water sources with a widespread mixture of highly pathogenic microorganisms and toxic chemicals . Consequently, providing safe technology for wastewater treatment has received significant attention and became an urgent concern for public health particularly in areas where contaminated water sources are used for different applications such as fish farms and crop irrigation, thereby eventually affecting the farmers and consumers .…”
Section: Introductionmentioning
confidence: 99%